Gambaran Subjective Well-Being Pada Mahasiswa Yang Berpacaran (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This research aims to investigate the level of Subjective Well-Being (Subjective Well-Being) in students who are dating in the university environment. Subjective Well-Being includes the psychological and emotional aspects of a person's life, including happiness, life satisfaction, and positive feelings towards oneself and the surrounding environment. romance This research sample consists of students from various study programs at various semester levels. In addition, this research also tries to identify factors that may affect the level of Subjective Well-Being in the context of romantic relationships. In addition, this research can also contribute to the literature of psychology and human development by providing additional insight into the emotional and psychological dynamics in romantic relationships in the student population.